Issues and challenges in voltage uprating for sustainable power operation: a case study of a 132 kV transmission line system in Malaysia - Mohd Nor, Shamsul Fahmi; Ab Kadir, Mohd Zainal Abidin; Mohd Ariffin, Azrul; Osman, Miszaina; Abd Rahman, Muhammad Syahmi; Mohd Zainuddin, Noorlina (MDPI AG, 2021)
Ageing grid infrastructure is a critical issue that is currently faced by electrical utilities worldwide, resulting in crucial decisions that must be made for the replacement, repair, or refurbishment of assets under constrained budgetary conditions, as well as other factors. As one of the fastest-developing countries globally, Malaysia is steadily growing in terms of its cumulative population, large industries, and advanced transportation sector, leading to an increasing electricity demand and, consequently, putting stress on electric utility providers to meet these tremendous demands. Significant concerns in the new development of transmission in Malaysia are the environmental issues, which involve exploration in gazetted areas and forest reserves. This paper describes the issues and challenges in developing a new transmission line system in Malaysia. In recent years, uprating existing transmission line systems has been one of the best asset management decisions for electric utility operators in order to meet such a demand for capacity. This paper assesses the technical issues and conventional methods of uprating the voltage of an existing transmission line system. The initial study found that the phase-to-Earth clearance does not fulfil the electrical clearance envelope. The study on the existing 132 kV transmission line system further analysed these issues and proposed an appropriate technique for uprating to a 275 kV transmission line system. Finally, the results indicate that the voltage uprating of the 132 kV transmission line system to 275 kV is able to satisfy the electrical clearance requirement envelope.